Is agricultural productivity in developing countries really shrinking? New evidence using a modified nonparametric approach - Nin-Pratt, Alejandro; Arndt, Channing; Preckel, P.V. (Elsevier, 2003)
Nonparametric productivity analyses performed to date show that most developing countries are experiencing relatively rapid technical regress in agriculture. We discuss the plausibility of these results and argue that they stem from the existence of biased technical change and the definition of technology used. We reestimate the Malmquist index for a group of developing countries using a different definition of technology and find that most developing countries in our sample are experiencing positive productivity growth with technical change being the main source of this growth.